Pengaruh FDR, BOPO dan Corporate Govarnance terhadap ROA dengan Fraud sebagai Variabel Moderasi Pada Bank Umum Syari’ah di Indonesia Periode 2014-2022 - Noeridha, Noorsyah Adi; Nurazizah, Putri Amalia (Journal of Applied Islamic Economics and Finance, 2024)
This study aims to determine the effect of FDR, BOPO and Corporate Governance on ROA with Fraud as a Moderating Variable in Islamic Commercial Banks. Corporate governance is proxied by the size of the board of commissioners. The population used in this study is Islamic commercial banks registered with the Financial Services Authority (OJK) in 2014-2022. The number of Islamic commercial banks sampled was 9 Islamic banks. The data used is secondary data in the form of annual reports obtained from the official website of each bank. Sampling was done by purposive sampling method. The research method used by the author is quantitative research with panel data regression analysis. The results of this study indicate that FDR and board size partially have a significant positive effect on ROA, BOPO partially has a significant negative effect on ROA. While the size of the board of commissioners and fraud partially has no effect on ROA. Fraud moderates as a pure moderator in the effect of BOPO on ROA and a moderator homologizer in the effect of FDR, board size and board size on ROA.